A mid-term estimate of 2018/2019 vaccine effectiveness to prevent laboratory confirmed A(H1N1)pdm09 and A(H3N2) influenza cases in Sicily (Italy). Issue 39 (16th September 2019) - Costantino, Claudio; Restivo, Vincenzo; Amodio, Emanuele; Colomba, Giuseppina Maria Elena; Vitale, Francesco; Tramuto, Fabio
Abstract: Influenza season started in Italy during the month of October 2018, approaching the epidemic peak in January 2019. This report aim to explore the mid-term virologic surveillance data of the 2018–2019 influenza season in Sicily and to estimate the effectiveness of seasonal influenza vaccine (VE) against A(H1N1)pdm09 and A(H3N2) influenza viruses. A test-negative design was used to evaluate influenza VE. In Sicily, almost all influenza infections were sustained by influenza type A viruses, of which 62.3% were A(H3N2) and 36.3% A(H1N1)pdm09. A reduction of laboratory confirmed influenza cases in Sicilian population immunized against influenza were observed. In particular, an overall significant protective values were observed for any influenza A viruses (Adj-VE = 44.0%; 95%CI: 11.2–64.7%), especially among 15–64 years old age group (Adj-VE = 59.5%; 95%CI: 0.03–83.1) and among the elderly (Adj-VE = 73.6%; 95% CI: 29.4–90.2).